2005
DOI: 10.1186/bcr1021
|View full text |Cite
|
Sign up to set email alerts
|

Mammary stem cells, self-renewal pathways, and carcinogenesis

Abstract: Bmi-1 = B lymphoma Mo-MLV insertion region 1; Dsh = Dishevelled; ESA = epithelial-specific antigen; Fu = Fused; GSK = glycogen synthase kinase; HBEC = human breast epithelial cell; Ihh = indian hedgehog; Ptch = patched; Shh = sonic hedgehog; Smo = smoothened; SuFu = suppressor of fused. Breast Cancer Research May 2005 Vol 7 No 3 Liu et al. AbstractThe mammary gland epithelial components are thought to arise from stem cells that undergo both self-renewal and differentiation. Self-renewal has been shown to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
305
0
22

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(344 citation statements)
references
References 67 publications
7
305
0
22
Order By: Relevance
“…Thus, deregulation of EMT-regulating factors in the mammary gland could induce EMT in epithelial mammary cells and/or in stem-like cells, and thus, these cells could later acquire mesenchymal characteristics with invasive and self-renewal capabilities, enabling these cells to develop micrometastasis and macrometastasis in distant organs. These data also support the hypothesis that breast cancer cells may have a stem cell origin (49)(50)(51).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, deregulation of EMT-regulating factors in the mammary gland could induce EMT in epithelial mammary cells and/or in stem-like cells, and thus, these cells could later acquire mesenchymal characteristics with invasive and self-renewal capabilities, enabling these cells to develop micrometastasis and macrometastasis in distant organs. These data also support the hypothesis that breast cancer cells may have a stem cell origin (49)(50)(51).…”
Section: Discussionsupporting
confidence: 77%
“…Other studies have shown that lower levels of p53 results in increased mammary stem/progenitors (Tao et al, 2011) and lack of pRb has been shown to promote expansion of multi-potent stem cells (Gutierrez et al, 2008). In addition, the ST antigen has been shown to activate Notch, Hedgehog and Wnt pathways (Ali-Seyed et al, 2006) all of which are associated with stem cell self-renewal as well as breast carcinogenesis (Liu et al, 2005). Furthermore, overexpression of telomerase is also known to enhance proliferation of adult stem cells (Sarin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the perturbations required for the tumorigenic transformation of these primitive cells remains unknown. Given the striking parallels between normal stem cells and cancer cells, including extensive self-renewal, expression of telomerase and ability to grow in anchorage-independent conditions (Liu et al, 2005), it is possible that these immature cells require fewer alterations for transformation compared with their more differentiated counterparts that lack these properties.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of human breast cancers show defects in Notch signaling, largely mediated by reduced expression of the Notch inhibitor, NUMB [41][42][43][44][45]. Evidence support that Notch plays a key role, in the regulation of asymmetric cell fate decisions in human mammary stem cells [41][42][43][44][45]. Notch activation requires the action of the proteolytic enzyme gamma secretase.…”
Section: Targeting Tics In Human Breast Cancersmentioning
confidence: 99%